Synthesis of Bis(1,2,3-Triazole) Functionalized Quinoline-2,4-Diones - Milićević, David; Kimmel, Roman; Gazvoda, Martin; Urankar, Damijana; Kafka, Stanislav; Košmrlj, Janez (Molecules (Basel, Switzerland), 2018)
Derivatives of 3-(1H-1,2,3-triazol-1-yl)quinoline-2,4(1H,3H)-dione unsubstituted on quinolone nitrogen atom, which are available by the previously described four step synthesis starting from aniline, were exploited as intermediates in obtaining the title compounds. The procedure involves the introduction of propargyl group onto the quinolone nitrogen atom of mentioned intermediates by the reaction of them with propargyl bromide in N,N-dimethylformamide (DMF) in presence of a potassium carbonate and the subsequent formation of a second triazole ring by copper catalyzed cyclisation reaction with azido compounds. The products were characterized by ¹H, 13C and 15N NMR spectroscopy. The corresponding resonances were assigned on the basis of the standard 1D and gradient selected 2D NMR experiments (¹H⁻¹H gs-COSY, ¹H⁻13C gs-HSQC, ¹H⁻13C gs-HMBC) with ¹H⁻15N gs-HMBC as a practical tool to determine 15N NMR chemical shifts at the natural abundance level of 15N isotope.
Keywords: Proton Magnetic Resonance Spectroscopy; triazoly; Copper; propargyl group; chinoliny; Quinolines; azido group; magnetická rezonanční spektroskopie s uhlíkem 13C; Triazoles; Carbon-13 Magnetic Resonance Spectroscopy; quinoline-2,4(1H,3H)-diones; click chemistry; bis(1,2,3‑triazole); protonová magnetická rezonanční spektroskopie; měď